2013
DOI: 10.1097/jcn.0b013e3182435f27
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Caregiver Congruence

Abstract: Several areas of HF clinical and research relevance, including self-care, advance care planning, and communication, were affected by congruence. Further research is needed to define how congruence is related to other relationship characteristics, such as relationship quality, how congruence can best be measured quantitatively, and to what degree modifying congruence will lead to improved HF patient and caregiver outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 25 publications
2
55
0
1
Order By: Relevance
“…This dyadic disconnect resulted in poor patient outcomes and was consistent with our findings. In addition, this study supports the finding of Retrum et al (2013), who found that incongruence and lack of communication in the patient–caregiver dyads affected HF disease management, perceived care needs, and EOL planning.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This dyadic disconnect resulted in poor patient outcomes and was consistent with our findings. In addition, this study supports the finding of Retrum et al (2013), who found that incongruence and lack of communication in the patient–caregiver dyads affected HF disease management, perceived care needs, and EOL planning.…”
Section: Discussionsupporting
confidence: 88%
“…As dyads interact in the role of patient and caregiver, these interactions are interdependent (Rusbult & Van Lange, 2003) and may show congruence and incongruence. Congruence is defined as consistent perceptions between the dyad regarding various aspects of the patient’s illness (Retrum, Nowels, & Bekelman, 2013). Incongruence in the dyad is defined as differences in decisions, behaviors, and attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this growing body of research, studies are focused on understanding patient and caregiver appraisal of the illness context and factors that contribute to incongruent appraisals (Cano, Johansen, & Franz, 2005;Lobchuk, Kristjanson, Degner, Blood, & Sloan, 1997;Lyons, Zarit, Sayer, & Whitlatch, 2002;Retrum, Nowels, & Bekelman, 2013). To date, however, few studies have examined the consequences of incongruence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, HF patient/informal caregiver dyads are currently undergoing careful examination in the cardiovascular nursing literature. 58 Recent dyadic studies have uncovered gradients of individual contributions and expertise in dyadic self-care, 5 incongruence between patient and caregiver perceptions of self-care 6,8 and the impact of self-care on dyadic quality of life. 7 This new focus on HF dyads comes with an associated need to study how dyadic dynamics influence self-care in greater depth.…”
Section: Introductionmentioning
confidence: 99%